Charpy impact test machine instrumentation using a PIC16F877 microcontroller - Lucena, Samuel Euzédice (Revista Ciências Exatas, 2008)
This paper presents an instrumentation design and development for a conventional Charpy impact ma-chine. The pendulum impact hammer has been adapted to receive a piezoelectric sensor to capture the hammer impact force against the specimen. A PIC16F877 microcontroller detects the instant impact and then digitalizes the 350 force samples, which are transmitted via UART serial port to a PC, where the samples are stored as an ASCII file. With the aid of graphics software (Origin® or Excel®), this procedure enables detailed analysis and data processing of force versus time of impact, thus allowing to obtain other important parameters on specimen behavior, besides the conventional Charpy machine data, the maximum applied force, energy to maximum force, the type of fracture, etc. The experimental results demonstrate that the developed instrumentation is feasible and aggregates enormous value to a classic Charpy impact machine.